2019
DOI: 10.1002/mrd.23131
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of O‐GlcNAc homeostasis during mammalian oocyte meiotic maturation impacts fertilization

Abstract: Meiotic maturation and fertilization are metabolically demanding processes, and thus the mammalian oocyte is highly susceptible to changes in nutrient availability. O-GlcNAcylation-the addition of a single sugar residue (O-linked β-N-acetylglucosamine) on proteins-is a posttranslational modification that acts as a cellular nutrient sensor and likely modulates the function of oocyte proteins. O-GlcNAcylation is mediated by O-GlcNAc transferase (OGT), which adds O-GlcNAc onto proteins, and O-GlcNAcase (OGA), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The current study is the first to detect and characterize O-GlcNAcylation in GCs of bovine antral follicles, but others have reported the existence of OGT and OGA enzymes, and expression of O-GlcNAcylated proteins, in cumulus oocyte complexes (COCs) [ 40 ]. Hyper-O-GlcNAcylation (via Thiamet-G), has no detrimental effects on the cumulus cells or the oocyte, but zygote formation following in vitro fertilization is compromised [ 40 ]. Other investigations report, however, that increased glucose shunting through the HBP (thus potentiating O-GlcNAcylation) has deleterious effects on oocyte health and developmental competence.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is the first to detect and characterize O-GlcNAcylation in GCs of bovine antral follicles, but others have reported the existence of OGT and OGA enzymes, and expression of O-GlcNAcylated proteins, in cumulus oocyte complexes (COCs) [ 40 ]. Hyper-O-GlcNAcylation (via Thiamet-G), has no detrimental effects on the cumulus cells or the oocyte, but zygote formation following in vitro fertilization is compromised [ 40 ]. Other investigations report, however, that increased glucose shunting through the HBP (thus potentiating O-GlcNAcylation) has deleterious effects on oocyte health and developmental competence.…”
Section: Discussionmentioning
confidence: 99%
“…TMG induced elevation of O-GlcNAcylation levels and kinetics is similar to that caused by cell stresses [ 19 , 34 , 44 , 45 ]. Moreover, TMG has been shown to increase O-GlcNAcylation in oocytes, leading to increased polyspermy [ 46 ], but it has not been used to treat pre-implantation embryos or trophoblast cells. The only previous attempt to elevate O-GlcNAcylation in pre-implantation embryos used the alternative OGA inhibitor PUGNAc [ 26 ], which is known to exhibit off-target effects [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…O-GlcNAc is recognized as an important regulatory mechanism of cytosolic and nuclear proteins (30). The involvement of O-GlcNAc in regulating mammalian oocyte maturation has been determined in previous literature (31,32). Frank and colleagues have reported that in vitro developmental competence of mouse oocytes was impaired by O-GlcNAc of heat shock protein 90 under hyperglycemic conditions (32).…”
Section: Oga Stability Was Modulated By Nat10-mediated Ac4c Modificationmentioning
confidence: 99%